A Conceptual Analysis of Strategies to Combat Organised Crime in South Africa. Issue 2 (July 2015) - Govender, Doraval
The general perception in South Africa is that organised crime is a rapidly increasing threat to the security of the country. Organised criminal groups usually start their criminal careers within police station precincts and move transnationally across police station borders, provincial boundaries, national and international borders. Since the 1980s, many effective strategies have been developed to combat organised crime internationally. Despite these strategies, local police stations in South Africa still use basic policing knowledge and skills to police organised crime at police station level. In the majority of cases, very little or nothing is done to confirm whether an arrested car thief, burglar or drug dealer belongs to an organised criminal group. The objective of this article is to identify the different strategies used internationally to combat organised crime, so that they may be used for designing and developing policy recommendations and operational responses to effectively combat organised crime. Given the scarce skills and knowledge of the local police to combat organised crime, this article recognises a need to empower local police officials to combat organised crime at the police station level.